Food taboos: their origins and purposes - Meyer-Rochow Victor (BMC, 2009)
Abstract Food taboos are known from virtually all human societies. Most religions declare certain food items fit and others unfit for human consumption. Dietary rules and regulations may govern particular phases of the human life cycle and may be associated with special events such as menstrual period, pregnancy, childbirth, lactation, and - in traditional societies - preparation for the hunt, battle, wedding, funeral, etc. On a comparative basis many food taboos seem to make no sense at all, as to what may be declared unfit by one group may be perfectly acceptable to another. On the other hand, food taboos have a long history and one ought to expect a sound explanation for the existence (and persistence) of certain dietary customs in a given culture. Yet, this is a highly debated view and no single theory may explain why people employ special food taboos. This paper wants to revive interest in food taboo research and attempts a functionalist's explanation. However, to illustrate some of the complexity of possible reasons for food taboo five examples have been chosen, namely traditional food taboos in orthodox Jewish and Hindu societies as well as reports on aspects of dietary restrictions in communities with traditional lifestyles of Malaysia, Papua New Guinea, and Nigeria. An ecological or medical background is apparent for many, including some that are seen as religious or spiritual in origin. On the one hand food taboos can help utilizing a resource more efficiently; on the other food taboos can lead to the protection of a resource. Food taboos, whether scientifically correct or not, are often meant to protect the human individual and the observation, for example, that certain allergies and depression are associated with each other could have led to declaring food items taboo that were identified as causal agents for the allergies. Moreover, any food taboo, acknowledged by a particular group of people as part of its ways, aids in the cohesion of this group, helps that particular group maintain its identity in the face of others, and therefore creates a feeling of "belonging".